2023
DOI: 10.3390/su15119073
|View full text |Cite
|
Sign up to set email alerts
|

Research on Spatial-Temporal Characteristics and Affecting Factors of Agricultural Green Total Factor Productivity in Jiangxi Province

Abstract: Increasing green total factor productivity is the key to achieving green development in agriculture. This study measured the green total factor productivity of Jiangxi’s agriculture, and its regional and temporal evolution characteristics were examined. The fixed-effects model was then used to investigate the model’s fundamental components empirically. The study’s findings reveal the following: During the period under review, technical change was the primary element driving the rise in the green total factor p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This study identifies the sources of green growth in Jiangsu's agriculture at the provincial, sub-regional and municipal levels, and finds that its growth is largely contributed to the effect of movement in the frontiers of technology; in other words, growth is mainly generated by advances in the green technology frontier led by pioneering practitioners, while the laggards' lack of enthusiasm in catching up with these frontiers is a bottleneck factor for growth. This result is broadly consistent with regional empirical studies measuring TFP growth in Chinese agriculture at the provincial level [22,26,30]. China's government-led agricultural STI system, through public agricultural R&D and extension networks, has achieved world-renowned success in increasing grain productivity; this includes the breeding of super-rice varieties and their large-scale dissemination among farmers.…”
Section: Green Growth Sources From Frontier Movement Effects or Catch...supporting
confidence: 83%
See 1 more Smart Citation
“…This study identifies the sources of green growth in Jiangsu's agriculture at the provincial, sub-regional and municipal levels, and finds that its growth is largely contributed to the effect of movement in the frontiers of technology; in other words, growth is mainly generated by advances in the green technology frontier led by pioneering practitioners, while the laggards' lack of enthusiasm in catching up with these frontiers is a bottleneck factor for growth. This result is broadly consistent with regional empirical studies measuring TFP growth in Chinese agriculture at the provincial level [22,26,30]. China's government-led agricultural STI system, through public agricultural R&D and extension networks, has achieved world-renowned success in increasing grain productivity; this includes the breeding of super-rice varieties and their large-scale dissemination among farmers.…”
Section: Green Growth Sources From Frontier Movement Effects or Catch...supporting
confidence: 83%
“…There has been much academic and policy interest in exploring China's agricultural growth in the context of market-led economic reforms via the introduction of this tool [19][20][21], as well as the regional heterogeneity of agricultural productivity changes [22,23]. Green development in agriculture has attracted a new wave of research [24,25], with much of the research focusing on how Green Total Factor Productivity (GTFP) [26][27][28] might be measured and its drivers explored [29][30][31]. To date, few studies have investigated the sources of such green productivity growth from the perspective of an STI system with Chinese characteristics, which is the policy value of the tool.…”
Section: Introductionmentioning
confidence: 99%
“…Table 8 demonstrates that when the logarithm of land transfer increased, the coefficient value of industrial agglomeration for agricultural green production efficiency declined from 0.611 to 0.218, and the t-value was reduced from 4.92 to 2.53, which indicated that there was a characteristic of a diminishing marginal effect of industrial agglomeration on the promotion of agricultural green production efficiency. A possible reason is that, on the one hand, the development of industrial agglomeration required continuous adjustment of the industrial structure to meet the market competition, and smooth land transfer is a necessary condition for bringing into play the effect of industrial agglomeration; however, frequent land transfer leads to an excessive adjustment of the planting structure, and production operators, out of the pursuit of profit maximization, turn from food crops to cash-crop planting, which relies more on chemical fertilizers, pesticides, and other chemicals, thus changing the original intensive production method and leading to a weakening of the effect of industrial agglomeration on the enhancement of agricultural green production efficiency through land transfer [59]. On the other hand, with the deepening of land transfer, land resources and production may be controlled by capital.…”
Section: Threshold Effect Models Testmentioning
confidence: 99%